(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Sarcomas are a rare and heterogeneous group of mesenchymal malignant tumors that account for less than 1% of all adult cancers and 12% of pediatrics cancers, apart from the tumors, location and grade, the histologic subtype of STS is a significant prognostic factor, Surgery, radiation, and chemotherapy are among the most common treatments for STSs today. Aim: This study aims to ascertain retrospectively the epidemiology and prognostic factors of soft tissue sarcoma and also highlights the outcomes in the terms of (overall survival) and (progression free survival) among Egyptian patients at clinical oncology and nuclear medicine department, Zagazig University and Ahmad Maher Teaching hospitals. Patient and Methods: Retrospective study of patients with non-metastatic extremities soft tissue sarcoma, these Study was done from two oncological centers in Egyptian Ahmed Maher teaching hospital and Zagazig University Clinical Oncology and Nuclear Medicine department, about 73 patient medical records from Jan 2010 till December 2021. Results: The median follow-up duration was 60 months (range; 11-72 months). Patients received by recording outcome of treatment we found that LRFS 45.5% over 5years while DMFS was 84.7% over 5 years and median disease free survival were 44.2% over 5 years, progression was seen in 3 patient With progression median time of 4 months, events accrued in 20 patient only With events free median time of 60 months and till now 58 patient mortality rates Were 20.5% and overall survival after 5 year were 70.7%. Conclusion: median overall survival (OS) for non-metastatic extremities soft tissue sarcoma was 72 months, median disease free survival (DFS) was 60 months, median distant metastasis free survival (DMFS) was 106 month and median event free survival (EFS)was 60 months, median progression free survival (PFS) was 4 months .